Hoje tirei uma foto minha - Camargo, Bruna; Lôbo, Maria Fernanda; Pedroza, Cecília; Gonsales, Bruno; Araújo, Gabrielle (Universidade Federal de São Carlos, 2021)
The movie traces the journey of the director/screenwriter as they craft their self-portrait and engage in a conversation with their identity as a woman with a disability. Using archival footage, performances, and off-screen narration, Bruna shares her life experiences, spanning from her childhood to the film's production. The film is driven by the absence of representation for people with disabilities in the media and the scarcity of images of the director during her adolescence and adult life. It serves as an exploration of subjectivity and the longing to create a visual representation of oneself. The movie bridges the concept of existence with the physical embodiment of the creator, especially when her perception of her body's presence in various spaces, both tangible and artistic, had been denied.
Today, I took a picture of myself
Keywords: Cinema; Audiovisual; Film; PCD; LINGUISTICA, LETRAS E ARTES::ARTES::ARTES DO VIDEO; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA::INTERPRETACAO CINEMATOGRAFICA